(untitled) (American Journal of Islam and Society, 2015)
This editorial is dedicated to paying a tribute to Professor Ali A. Mazrui, who passed away in Binghamton, New York, on October 13, 2014. From 2009 (AJISS 26:1) until his passing, Professor Mazrui was the editor-in-chief for this journal. In years to come, we may consider dedicating a special issue to him and his general intellectual contributions. But for now, we present the following tribute penned by his friend and colleague, Professor Sulayman S. Nyang (Howard University, Washington, DC), as published in IIIT “Special Issue: Farewell Professor Ali Mazrui” (October 2014). Professor Ali A. Mazrui, the celebrated scholar, author, and public intellectual from Kenya came, performed, and departed gracefully. Certainly, those who knew him well gladly fared him well, knowing beyond reasonable doubt that he had the nerve and the verve to represent both Islam and Africa faithfully and effectively. It is against this background that one can examine a profile of the man and his legacies within many domains in America, the Islamic world, and in the larger world ...